Evaluation of Analgesic and Anti-inflammatory Effects of a Poly-herbal Ayurvedic Formulation (Bangladesh Pharmaceutical Journal, 2013)
A poly-herbal ayurvedic formulation containing Sida retusa (root), Withania somnifera, Frillaria roylei, and Paederia foetida (prasarini) is used in the treatment of inflammation and pain based on the long-term experience of the ayurvedic physicians, but no scientific study has been carried out so far. We have evaluated the analgesic and anti-inflammatory activities of the poly-herbal preparation using different animal models such as hot plate method for analgesic activity and anti-inflammatory activity by carrageenan-induced inflammation. Significant analgesic activity of the poly-herbal formulation was found after 2 hours as compared to the control. The product also showed sufficient anti-inflammatory activity while checked against carrageenan induced inflammation. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14492 Bangladesh Pharmaceutical Journal 16(1): 59-62, 2013